2004
DOI: 10.1002/ctpp.200410062
|View full text |Cite
|
Sign up to set email alerts
|

Progress of the Electron Kinetics in Spatial and Spatiotemporal Plasma Structures

Abstract: A brief introduction into the progress of the analysis of the electron kinetics in spatially one-and two-dimensional steady-state plasmas and in spatiotemporal transition processes of spatially one-dimensional plasma configurations is given. The wide spectrum of the involved kinetic problems is briefly characterized, main aspects of its kinetic studies are outlined and the progress reached in recent years is illustrated by the kinetic study and deduced results of some selected problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The correct description of the FH experiment, which intends to go beyond qualitative explanations, requires a treatment at the level of the kinetic theory [12,13] due to the appearance of nonequilibrium effects [14] in the electron transport. We emphasize that the term "nonequilibrium" is used here to characterize transport and not the thermodynamical state of the system.…”
Section: Introductionmentioning
confidence: 99%
“…The correct description of the FH experiment, which intends to go beyond qualitative explanations, requires a treatment at the level of the kinetic theory [12,13] due to the appearance of nonequilibrium effects [14] in the electron transport. We emphasize that the term "nonequilibrium" is used here to characterize transport and not the thermodynamical state of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Exact description of the electron behavior can be obtained by solving the kinetic Boltzmann equation. [17][18][19][20] However, this approach is mathematically very complicated, especially if more than one dimension needs to be simulated. Method known as particle in cell/Monte Carlo collisions (PIC/MCC) 21,22 which couples MC simulations for the behavior of electrons and ions to the Poisson equation for the self-consistent electric field, is also time consuming, and has not come into wide use in the glow discharge plasma modelling.…”
mentioning
confidence: 99%
“…In these and further [29,30] studies it has generally been found that a kinetic approach is required and that the deduced microscopic and macroscopic behaviour of the electrons strongly depends on the specific problem considered. A common result of the analyses is that a pronounced non-local response of the electron gas takes place e.g.…”
Section: Kinetics Of the Electronsmentioning
confidence: 98%